2018
DOI: 10.1186/s13072-018-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic prediction of DNA shape changes due to CpG methylation explains epigenetic effects on protein–DNA binding

Abstract: BackgroundDNA shape analysis has demonstrated the potential to reveal structure-based mechanisms of protein–DNA binding. However, information about the influence of chemical modification of DNA is limited. Cytosine methylation, the most frequent modification, represents the addition of a methyl group at the major groove edge of the cytosine base. In mammalian genomes, cytosine methylation most frequently occurs at CpG dinucleotides. In addition to changing the chemical signature of C/G base pairs, cytosine met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 50 publications
2
54
0
Order By: Relevance
“…However, the most frequent of all epigenetic markers in DNA is cytosine methylation. This change in the human genome is referred to as “CpG methylation” or “DNA methylation” [ 52 ]. Inactivation of tumor-suppressor genes (TSGs) is caused by overall DNA hypomethylation and hypermethylation of CpG islands located in the closest vicinity of the promoter.…”
Section: Resultsmentioning
confidence: 99%
“…However, the most frequent of all epigenetic markers in DNA is cytosine methylation. This change in the human genome is referred to as “CpG methylation” or “DNA methylation” [ 52 ]. Inactivation of tumor-suppressor genes (TSGs) is caused by overall DNA hypomethylation and hypermethylation of CpG islands located in the closest vicinity of the promoter.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier line of work it was shown that CpG methylation in DNase I cut sites increases cleavage efficiency by altering the DNA structure (54), which can also be predicted by looking at DNA shapes (55). To systematically compare the enzyme specific sequence preferences within each assay we predicted structural DNA shape features (see Methods) around the GpC methylation sites (NOMe) and the enzyme cutting sites (ATAC, DNase I) (Figure 3B and Figure S6) across a number of available samples and datasets (see Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…41 Another study showed that CpG methylation significantly altered local DNA shape. 42 DNA methylation is closely linked with the occupancy patterns of an important genome regulator, CTCF, which binds to insulator regions in genomic DNA and plays a fundamental role in controlling higher order chromatin structure and gene expression. 43 To decipher whether CTCF binding plays a role in the link between DNA methylation and cell morphological changes, more comprehensive DNA methylation datasets including noncoding regions such as bisulfite sequencing together with image data are needed to expand our work.…”
Section: Discussionmentioning
confidence: 99%